2022
DOI: 10.3390/md21010006
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of a New Cold-Adapted and Alkaline Alginate Lyase TsAly7A from Thalassomonas sp. LD5 Produces Alginate Oligosaccharides with High Degree of Polymerization

Abstract: Alginate oligosaccharides (AOS) and their derivatives become popular due to their favorable biological activity, and the key to producing functional AOS is to find efficient alginate lyases. This study showed one alginate lyase TsAly7A found in Thalassomonas sp. LD5, which was predicted to have excellent industrial properties. Bioinformatics analysis and enzymatic properties of recombinant TsAly7A (rTsAly7A) were investigated. TsAly7A belonged to the fifth subfamily of polysaccharide lyase family 7 (PL7). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…For example, rTsAly7A derived from Thalassomonas sp. LD5 has shown the highest activity at 100 mM NaCl and was twice as active as it was at 0m NaCl [ 21 ]. One study has shown that the salt activation mechanism of AlyC3 is to preserve a dimeric quaternary structure.…”
Section: Resultsmentioning
confidence: 99%
“…For example, rTsAly7A derived from Thalassomonas sp. LD5 has shown the highest activity at 100 mM NaCl and was twice as active as it was at 0m NaCl [ 21 ]. One study has shown that the salt activation mechanism of AlyC3 is to preserve a dimeric quaternary structure.…”
Section: Resultsmentioning
confidence: 99%
“…However, despite the merits of the enzymatic method for AOS production, two challenging issues impede its development. Firstly, the products of endotype alginate lyases are typically a mixture of AOS at degrees of polymerization (DPs) ranging from 2 to 6 [19][20][21]. The considerable heterogeneity of AOS products results in instability and variability regarding their biological activity.…”
Section: Introductionmentioning
confidence: 99%